Limites formais e materiais ao controle de constitucionalidade pelo Supremo Tribunal Federal - Macedo Filho, Cícero Martins de (2006)
This document approaches the formal and material limits of the constitucionalidade control for the Supreme Federal Court, iniating with the study of the Constitution, detaching its evolution, nature and meanings, passing for its historical evolution, offering still a unconstitutionality concept. Is work the principles as material Constitution, making the distinction entere principles and rules, detaching the characteristics of the principles constitutional, and the basic principle of the Constituition. It analyzes metodologics the historical parameters and of the brazilian system of constitutionality control and detaches the paper of the Supreme Federal Court as positive legislator. It observes the beddings of the constitutionality control and the legitimacy of the Supreme Federal Court. Is examines the performance of the Supreme Federal Court in face of the principle of the legal security. Is offers a vision on the experience of the control of constitutionality in other constries. It still approaches the control of constitutionality in Brazil, detaching the critical points of its formal and material limits. Is verifies the application of the principles constitutional for the Supreme Federal Court in the diffuse control and the intent control of constitutionality, as well as the performance of the Supreme Federal Court ahead of the unconstitutional omissions. It brings to the debate the new perspectives how much to the formal and material limits of the control of constitutionality for the Supreme Federal Court. Objective to elaborate considerations concerning the limits of the constitutional jurisdiction from the model of Constituition, the character politican of the difficulties with respect to the definition of its formal and material limits from the performance of the Supreme Federal Court